Building Practical Authority for Community Forestry in and through Networks: The role of community‐based organisations in the U.S. West. (14th June 2017) - Abrams, Jesse; Davis, Emily Jane; Moseley, Cassandra; Nowell, Branda
Abstract: Policy and economic changes in the late 20th century fundamentally reorganized the governance of public forestlands in the US West, throwing longstanding rural development trajectories into disarray. Place‐based NGOs emerged across the West in the wake of this transformation to help rural communities gain access to the benefits of new restoration‐oriented management paradigms. Here we analyse the practical efforts of two of these community‐based organizations, Wallowa Resources and the Watershed Research and Training Center, as they attempt to implement community forestry practices in highly complex institutional environments. We focus on the ways in which these organizations access and utilize social networks at multiple scales in order to build the 'practical authority' necessary to lead institutional change efforts in and on behalf of rural communities. We consider both the strategic advantages and the practical challenges of working in multiple forums at multiple scales in pursuit of linked community and environmental benefits. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment